Resolution Of Land Disputes Through Mediation Study At The National Land Agency Of Central Lombok, West Nusa Tenggara, Indonesia - Pratama, Buyung Alfian; Sudiarto; Kaharudin (Faculty of Law, University of Mataram, 2025)
The ongoing development of human life, coupled with the imbalance in land availability, has led to serious consequences for the relationship between land and humans. One major consequence is the growing demand from the community for civil rights, making land disputes inevitable. The resolution of land disputes through the courts is often seen as inadequate, prompting efforts for resolution through mediation. Mediation related to land is governed by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN Number 21 of 2020 concerning Handling and Settlement of Land Cases. This study aims to analyze and understand the extent of the implementation of the Agrarian Ministerial Regulation/Head of BPN RI No. 21 of 2020, as well as the supporting and inhibiting factors in the mediation process. The theories utilized in this study include the theory of justice, the theory of legal certainty, the theory of legal protection, and the theory of dispute resolution. The study employs an empirical legal research method, utilizing a statutory approach, a case approach, and a conceptual approach. The findings indicate that, in the implementation of mediation at the BPN of Central Lombok, the regulatory reference used is Article 44 of the Agrarian Ministerial Regulation/Head of BPN Number 21 of 2020. This implementation involves several stages: submission of applications, document examination, mediator appointment, the mediation process, and the execution of mediation agreements. The supporting factors for mediation include the willingness of the parties, the competence and neutrality of the mediator, the availability of clear administrative evidence, government and institutional support, and the presence of solutions that benefit all parties. The inhibiting factors for mediation are the uncooperative attitudes of the parties, unclear land statuses, external influences, and the lack of strict sanctions for uncooperative parties.